INFORMATION SERVICES PROVISION OF THE PUBLIC LIBRARIES TO PEOPLE LIVING WITH HIV/AIDS (PLWHA) IN ANAMBRA STATE, NIGERIA (NAU Journal of Library and Information Science, 2021)
This study investigated information service provision of public libraries to people living with HIV/AIDS (PLWHA) in Anambra State, Nigeria. The study was carried out using a descriptive survey design with two research questions.The population of this study comprised of 5,385 adult male and female PLWHA registered in Nnamdi Azikiwe University Teaching Hospital, Nnewi. The sample is 385 PLWHA. Purposive sampling technique was used to sample the number of respondents for this study. The researcher major findings are that some of the services provided by the public library to PLWHA are reading materials, chairs and tables, referral services, bibliographic services, literature search and lending services; while some of the ones not provided are: document delivery services, weekend library services, recreation services, film show services, career information service and notification of conferences, seminars and workshop services. Based on the findings, it was recommended among others that the government should ensure that any constraint facing the provision of adequate library information services should be tackled. Keywords: Information Service Provision, Public Libraries, PLWHA, Pharmaceutical Library, Nnewi.Introduction A public library is a library whose services is meant to serve the general public. It is a layman’s university usually funded by the state government with branches in various parts of the state. The public libraries provide information services that are for every individual, whether literate or illiterate and for variety of issues essential for his or her survival (Mooko & Aina, 2007).The public library as an institution, affords opportunities for lifelong learning, empowerment, better living and overall development of individuals and groups (Oyegade, Nassarawa & Mokwugo, 2003). The public library institution is an acknowledged agent that provides reliable information and materials capable of enlightening the populace. This information is made available to varied individuals with different needs, motives, drives, perceptions, requirements and behavioral patterns (Osuigwe, 2012). According to Kolawole (2012) the public library is one channel by which relevant issues and information are passed to people either in print or non-print. This information is needed in all spheres of life to facilitate decision making and engender progress.Public libraries exist as key resources in their communities. The essence and purpose of establishing the public library lies in the need for availability of accurate, updated and unswerving information and the benefits adequate usage of such information would have on the individual. It is common knowledge that information is power and when it is properly applied, it is more powerful, while lack of knowledge is a huge factor militating against progress in every sphere of human endeavor. Most times in Africa, the intended community of users is not aware of public library services while on the other hand awareness may be there but the information and/or the services needed at a time may not be available. Therefore, public library services would be beneficial when the various services are brought to the knowledge of the populace especially in the 21st century when the society is facing the challenges of HIV/AIDS, Ebola, MERS, Zika Virus and other such diseases that need prompt and dependable information for prevention, management and curbing the spread through timely knowledge.Health is a predisposing factor for development. The third goal of the UN 2030 Agenda highlights the need for healthy lives and the promotion of well-being for all at all ages (UN, 2016). Human Immunodeficiency Virus and Acquired Immunodeficiency Syndrome HIV/AIDS, remains one of the most significant public health challenges in current times, and certainly one of the biggest obstacles to socio-economic development especially in developing countries (WHO, 2011).HIV is a virus while AIDS is a medical condition (Nordqvist, 2012). The major difference between HIV and AIDS is that HIV is the virus which attacks the T-cells in the immune system while AIDS is the syndrome which appears in advanced stages of HIV infection. The disease alters the human immune system, making the sufferers much more vulnerable to infections and diseases. This susceptibility worsens as the disease progresses (Medical News Today, 2013).HIV/AIDS infection in Nigeria remains a major public health crisis. In Nigeria, the first case of HIV/AIDS was reported in 1986 and the prevalence rate has been increasing progressively since then (UNAIDS, 2007). HIV prevalence among adults aged 15–49 years, increased from 1.8% in 1991 to 5.8% in 2000 (Federal Ministry of Health, Nigeria, 2002, 2005). However according to UNAIDS (2007) and USAIDS and PEPFAR (2008), HIV prevalence has further declined to 3.9% by 2006. Although the prevalence rate is lower than it is in South Africa, it is estimated that about 2.98 million people are living with the virus in Nigeria (UNAIDS, 2007). Nigeria has the second highest number of People Living with HIV/AIDS (PLWHA) in the world after South Africa (USAID, 2010). The epidemic has affected all the geographical zones, urban and rural locations in the country with very wide variations. In Anambra State 166,237 persons are living with HIV/AIDS which is about 8.7% of infected people in Nigeria (Nigerian Agency for Control of AIDS, 2013). Anambra State is in the fourth position of the highest numbers of PLWHA in Nigeria after Rivers State, Akwa Ibom State and Benue State. More than 80% of HIV transmission in Nigeria is mostly through heterosexual sex.The awareness of being infected generates identity crises, isolation, loneliness, low self-esteem and lack of interest in curtailing further spread of HIV/AIDS. PLWHA lack motivation to practice preventive measures and acquire information that will improve their health status, lifestyle and existence. Fears of death associated with HIV reduce care-seeking behavior among carriers. HIV infected individuals may face termination of appointment, hostility, denial of gainful employment, forced resignation or retirement (Emmanuel and Andrea, 2012). This infringement of their rights is exacerbated by the negative lifestyle exhibited by PLWHA. The effects of HIV/AIDS pandemic on individual and family include: illness and suffering, shortened life span, loss of work and income, death of family members, grief, poverty, trauma, stress, anxiety, fear, despair and barrier to healthcare services due to stigma and discrimination. Furthermore, deteriorating child health and survival as well as weakened integrity, transmission of infection, burden of nursing care, impoverishment, and infringement of children’s right such as education are also effects of HIV/AIDS pandemic on the society. Losses of family assets and regards, parental loss and in most cases self-stigmatization are also fall-outs of HIV/AIDS pandemic.It is expected of the public libraries in Nigeria to render some information services which will help to create a knowledge balance for its users, particularly PLWHA. Some of the services include: Internet services, loan services, reference services, selective dissemination of information (SDI), information resources, and translation services. If these services are effectively provided, the inherent benefits associated with such services will be gained by the users. In this study, the researcher tries to ascertain if the services are provided and how the users feel about its benefits.According to Iwhiwhu (2008), public library services most often provided are abstracts, newspaper indexing, SMS information services, information repackaging in vernacular, mobile library services, Internet services, lending services, references, SMS alerts, film shows, special collections, display among others. Public libraries also engage with groups of people with specialized information needs in order to create and provide targeted library and information services particularly suited for them.Although major advances in treatment have prolonged and improved the quality of life of those infected with HIV there is still no cure for or a vaccine to prevent this deadly disease. Perhaps, most importantly, it has become increasingly clear that primary prevention must focus on information on risky behavioral lifestyles to avoid infection while the management/treatment of PLWHA ought to encompass the learning and adapting to new lifestyles. Information services provided by the public library could be highly beneficial to PLWHA and people not with HIV/AIDS to forestall risky lifestyle. This might help to reduce the spread of HIV/AIDS through lifestyles choices.Statement of the ProblemInadequate understanding of HIV/AIDS by PLWHA propels the spread of the disease as they adopt risky behavior thus easily exposing themselves to secondary infections and the continued spread of the disease. More so, the inability of the citizenry to knowledge and access correct information about HIV/AIDS and probable unavailability of such information promotes stigmatization and discrimination of PLWHA as they are assumed to be promiscuous. HIV/AIDS being regarded as a death sentence makes PLWHA desperately prone to accepting information from quacks and pretentious faith healers thus endangering their health status further. Accurate information provides the framework for informed decisions which could be of immense benefits to PLWHA. The central question therefore posed by this study is, are the needed pieces of information available when and where they should be? The public library is trusted for ages as an institution that provides correct information to the general public, which include; the old, young, handicapped persons and even PLWHA. If this assertion is true, then the question is, what are the information services provision by the public library for PLWHA; to what extent are these services provided and what are benefits of these services to PLWHA? The answer to these questions is the main focus of this study.Purpose of the StudyThe purpose of this study was to establish the information services provision of public libraries to People living with HIV/AIDS(PLWHA). Specifically, the study sought to:1. ascertain the information services provision of the public libraries to PLWHA in Anambra State; and2. examine the users’ (PLWHA) level of satisfaction with the provided information services.Research QuestionsThe following research questions guided the study:1. What are the information service provisions of public libraries to PLWHA in Anambra State?2. What is the users’ (PLWHA) level of satisfaction with each of the information services provided?MethodologyThe design of this study is a survey (descriptive and inferential) in the sense that the researcher collected data from a sample and used descriptive statistics to answer the questions. The population of the study is 5,385 adults (male and female) PLWHA registered in the Nnamdi Azikiwe University Teaching Hospital, Nnewi. These are PLWHA who have been in care for a period of three years and above, and were on visit within the period of the study. The sample is 385 PLWHA. The researcher used purposive sampling technique to get the number of respondents for this study. Purposive sampling technique enabled the researcher to focus on particular characteristics of the population that are of interest, which best enabled her to answer her research questions. Adult males and females PLWHA that have been in care for 3 years and above were purposively selected. The rating scale and interview were used to collect data for the study. The distribution of the instrument was carried out on week days except on Fridays when less PLWHA come for visit. A period of one month was allotted for the distribution and collection of the instrument in the clinic. Copies of the instrument were administered by the researcher with the help of some PLWHA staff (treatment support specialists -TSS). English and native languages were used for further clarification where necessary.Support staff and three treatment support specialists helped the researcher.The three treatment support specialists were instructed on communication skill and how to engage the respondents to ensure that the rating was administered and filled. In addition, they were instructed on how to explain to the respondents that the data being collected was confidential but would help to generate data that would improve public library services that would be of benefit to PLWHA. Since it was on- the-spot distribution and collection, at the end of the administration, all the 385 copies were retrieved without any loss.The rating scale is titled “Information Services Provision by Public Libraries to PLWHA and Benefits Scale (ISPPLPB)” with 117 items, which was designed for PLWHA. It consisted of two sections based on the research questions. Section A is on the bio data of the respondents while Section B addressed the research questions. The instrument was designed using four-point scale Clusters A and D were rated with Strongly Agree, Agree, Disagree and Strongly Disagree, Cluster B was rated using Very Satisfied (VS), Satisfied (S), Fairly Satisfied (FS) and Not Satisfied (NS), while Cluster C was rated with Most Often (MO), Often (O), Fairly Often (FO) and Not Often (NO). Their rating points were 4, 3, 2 and 1 respectively. The written interview was administered to the two librarians heading the Awka and Nnewi libraries respectively.Data collected through the rating scale were analyzed so as to get: some descriptive statistics ‘arithmetic mean’ and ‘standard deviation’ to answer research questions. The value 2.50 is taken as the criterion expected mean for answering research questions based on item by item considerations. Any item with mean score of 2.50 or above was considered as having been agreed upon by or satisfying to by the respondents, while any mean below 2.50 was regarded as otherwise.Results Table 1Table 1 shows the mean ratings of the respondents on information services provided to PLWHA by the public libraries in Anambra State. The result shows that the PLWHA were provided with enough information services through the reading materials, provision of chairs and tables, referral services since it attained a mean score of 3.29 which is above the value mean criterion of 2.50. on the other hand, information services provided through delivery services, weekend library services, recreation services, film show services, career information service and notification of conferences, seminars etc has a mean criterion of 1.82. The result shows that because it was below the value criterion of 2.50 PLWHA’s were not provided with adequate information services from them.Result from the interview conducted on the two Heads of the public libraries studied shows that the following information services were provided: material, tables and chairs services, computers services, reference services, bibliographic services lending services, information resources and literature search services. They are among the services agreed upon by the PLWHA as provided, though fewer in numbers.Table 2Table 2 shows the mean ratings of the respondents on users’ (PLWHA) level of satisfaction with each of the provided information services. The PLWHA, who responded on the average, indicated their satisfaction considering mean criterion of 3.13. This shows that provision of reading materials, provision of chairs and tables, referral services etc. were satisfactorily above the value of mean criterion 2.50. However, they were not satisfied with other items since the mean criterion of 1.82 was below the value of mean criterion of 2.50. The services which they were not satisfied with were lending services, delivery services, weekend library services, recreation services, film show services, career information service and notification of conferences, seminars, workshop services etc.Interview result from the librarians indicated that the PLWHA were not satisfied with the information services to a high extent.Discussion of FindingsIt was found in this study that some of the services provided by the public library to PLWHA were provision of reading materials, chairs and tables, referral services, bibliographic services, literature search and lending services; while some of the services not provided were: document delivery services, weekend library services, recreation services, film show services, career information service and notification of conferences, seminars and workshop services. This implies that most of the services were not provided in the public library. This finding was confirmed by the grand mean score of 2.17 PLWHA on the information services provided to them by the public libraries in Anambra State is not significantly greater than the criterion mean 2.50 this implies that the respondents agreed that provision of library information services is below the stated criteria. In line with this finding, Ikenwe and Adegbilero-Iwari (2014) in “Utilization and user satisfaction of public library services in South-West Nigeria in the 21 st century: A survey” results showed that the services mostly in use by users of the four state library boards were Users’ education (71.8%), Reference Services (69.4%), lending of materials (53.7%) and current awareness services (60.8%). Even though extension services, adult literacy services, and translation services are very essential services in any public library, it was revealed that these services were not in use by these users. Also, it was revealed that only (6.6%) of the users of the four public libraries had used Computer/ ICT services before in the library. This implied that ICT services were acutely poor in Nigerian public libraries and probably not available but just computers. The findings of Mehra and Dessel (2011) in “The role of library and information science education in the development of community health information services for people living with HIV/AIDS: Perspective of director and managers of public libraries” showed that the Knox County Public Library system provided few and outdated materials on HIV/AIDS (e.g. books, magazines) to electronic sources and authoritative websites on the subject. With this in place, Bamise, Bamise and Adedigba (2009) study in “information needs of people living with HIV/AIDS in Ibadan metropolis” revealed low utilization of their AIDS information services. This is because the provisions of the services are not adequately available. The similarities recorded in the above findings may imply that the studies could have used similar in nature of respondents.It was further found in this study that the respondents are satisfied with the following information services: provision of reading materials, provision of chairs and tables, referral services, bibliographic services, literature search etc. however, they were not satisfied with document delivery services, weekend library services, recreation services, film show services, career information service and notification of conferences, seminars, workshop services etc. The study then established that the mean score 2.46 of PLWHA on their level of satisfaction with the provided information services is not significantly greater than the criterion mean 2.50 This is a clear confirmation that the information services are below expectations. In consonance with this finding, Tiemo and Ateboh (2016) study in “User satisfaction with library information resources and services: A case study college of health sciences library Niger Delta University, Amassoma Nigeria” showed that users were satisfied with the lending services of library, renewal of library materials and longer hours of internet services in the library. It was also revealed in the study that users were dissatisfied with the limited reference materials in their various subject areas, national and international journals because they were not up to date. This implies that most services are not satisfactory to the clients. Also, Nnadozie, Okeke and Onyekweodiri (2015) in “User satisfaction in public libraries result shows that some respondents were satisfied with the collection of newspapers/magazines (36.7%), easy accessibility of the libraries (31.2%), as well as the stock of materials on local history i.e. Nigeriana (22.5%). On the other hand, many others were dissatisfied with the out-dated (30%) and deteriorating (25%) nature of the available titles, as well as the unavailability of desired information sources, including ICTs (21.2%). Overall, more respondents were dissatisfied (74.1%) with available resources, facilities and services compared to the 15.4% that were satisfied. Bamgbose, Oyesola and Ogunmodede (2014) in “Information needs of people living with HIV/AIDS in Ibadan Metropolis” revealed that none of the respondents visited the counselors; some could not access the needed information due to poverty. The similarities here may be attributed to similar areas of study.Conclusion This study investigated information service provision of public libraries and its benefits to people living with HIV/AIDS (PLWHA) in Anambra State, Nigeria. The public library is a social institution established on the principle of democracy of free access to information for every individual in the community irrespective of religious, economic or health status. Thus, the public library provides basic conditions for lifelong learning and informed independent decision making. Studies have shown that in as much as library and information services for HIV/AIDS could assist in bringing down the prevalence rate through information services, the use of social media services have also in greater capacity information services that can influence PLWHA’s to live positively and live fulfilled life.Library services are regarded as social services which are bound to stimulate the reading habit in the society. For the rural library to be functional, the services it provides should correspond with the needs of its users because the user is the very reason for the existence of the library and it ensures that the services so provided are exploited to the maximum. Any library that wants to improve its services to meet the needs of its users must strive to ascertain their information needs beforehand.RecommendationsBased on the findings, the researcher recommended as follows:1. The public libraries can go into partnership with private organization to enable them provide the needed services in the library as the library budget continues to dwindle.2. Additional efforts should be made by all stakeholders to see that PLWHA are satisfied with the services provided to them.3. Library services should be provided as often as possible, so that whenever they come to make use of the services, they will not be disappointed.ReferencesAction Aid International (1990). HIV and AIDS. Retrieved from: www.actionaid.org.Akanwa, P. C. (2013). Public library services to children in rural areas. Library Philosophy and Practice, Retrieved from: http://digitalcommons.unl.edu/libphilpr ac.Anambra State Government History(2014).Retrieved from: http://www.anambrastate.gov/ .Anambra State Ministry of Health FHI 360, UNICEF and USAIDS (2013). Operational plan for elimination of mother-to-child transmission of HIV in AnambraState, Nigeria. Retrieved from: www.fhi360.org/sites/Anambra%20state20op%20plan/ Anambra State, Nigeria (2013). People and local government Areas, Retrieved from : http://www.ngex.com/nigeria/places/state/anambra.htm /Ape, R., Uganneya, S. & Ode, M. (2012). Methods employed by public libraries in providing services to people living with HIV and AIDS in Benue State, Nigeria. The Information Technologist, 9(2). Retrieved from: http://www.ajol.info/index.php/ict/article/view/87077 Arinola, A.A. &Adekunji, O.A. (2012). Analyses of HIV/AIDS information awareness and effectiveness among artisans in Ogbomoso, Oyo State, Nigeria.Library Philosophy and Practice. Retrieved from: www.academicjournal.org/ .Asemah, E. S., Gujbawu, M., Ekhareafor, D.O. &Okpanachi, R.A (2012). Research method and procedure in mass communication. Jos: Great Future Press.Batambuze, C. (2003). The role of libraries in providing access to information for children and young adults with special attention to AIDS issues. World Library and Information Congress: 69th IFLA General Conference and Council, Berlin. (1-9 August 2003). Retrieved From: www.ifla.org/IV/ifla69/papers/041e-Batambuze.pdf Ebiwolate, B. P. (2010). Nigeria public library services to rural areas: Libraries in Niger Delta States. Library Philosophy and Practice. Retrieved from:http:unilib.edu/LPP/.Edewor, N. (2010). Access to health information by people living with HIV/AIDS inNigeria. Library Philosophy and Practice. Retrieved From: digitalcommons.uni.edu/cgi/viewcontent.cgi?article=1328&context/Emmanuel, M., Andrea, S. & James, E. (2012). HIV/AIDS related stigma and discrimination in Nigeria: Review of research studies and future directions for prevention strategies.Retrieved from:en/index.html.Enem, N., &Omekwu, C. (2014) Federal Ministry of Health (FMH). Nigeria HIV/AIDS: What it means for Nigeria background, projections, impacts, Hallman, K. (2004). Socio-economic disadvantage and unsafe sexual behavior of young women and men in South Africa. Policy Research Division Working Paper No 190. Population Council, New York.http:/wwwpopulationcouncil.org/.Ikenwe, I., &Adegbilero-Iwari, I (2014). Utilization and User Satisfaction of Public Library Services in South-West Nigeria in the 21st Century: A Survey. International Journal of Library Science, 3 (1).Isabella, A. &Dhanavandan, S. (2014). Usage and awareness of public services: An exclusive study on rural women.International Journal of Digital Library Services. Retrieved from: www.Isrj.in/ArchiveArticle.aspx?id=21/Issifou Y. et al (2014). Sexual risk behaviour among people living with HIV and AIDS on antiretroviral therapy at the regional hospital of Sekode, Togo. BMC, Public Health, 14:636.Iwhiwhu, E.B. (2008). Information repackaging and library services: A challenge to information professionals in Nigeria. Library Philosophy & Practice.Kasum, P., Verma, N. &Jadam, A. (2013). Information and Communication Technology(ICT)basedlibrary system: Anintroduction. Acme InternationalJournal of Multidisciplinary Research (AIJMR) 1 (2), 4-8.Medical News Today (2013). http://www.medicalnewstoday.com/article/17131.phd, Mehra,B., &Dessel. A (2011). The Role of Library and Information Science Education in the development of Community Health Information Services for People Living with HIV/AIDS: Perspective of Directors and Managers of Public Libraries.Momoh, S. O., Moses, A. I. &Ugiomoh, M. M. (2006). Women and the HIV/AIDS epidemic: The issue of school girls’ awareness in Nigeria. Journal of International Women’s Studies, 8(1), 212-218.Mooko, N., &Aina, L.O. (2007). Information environment of artisans in Botswana. Journal of Library and Information Science, 57(1),27-33.Nnadozie, C., Okeke, I., &Onyekweodiri (2015). User Satisfaction in Public Libraries in South-East Zone of Nigeria. Retrieved from:https: www semanticscholar.orgOnyeneho, N.G. (2009). HIV/AIDS risk factor and economic empowerment needs of female sex workers in Enugu Urban, Nigeria. Journal of Health Research, 11(5),126-135.Oyegade, E.A., Nassarawa, A. &Mokwugo.A. (2003). Forty years of public library services in Nigeria. In: S.O. Olanlokun (Ed.). Forty years of library services in Nigeria. Lagos: Ikofa Press.Osuigwe, N. (2012). In quest of academic achievement: A public library’s partnerships in Onitsha, Anambra State, South East Nigeria. In: Karen, Ellen (Ed). Partnerships and collaborations in public library communities: Resources and solutions, (39-51).Osuigwe, N.&Jiagbogu, O. U. (2015). Information for the control of the spread of HIV among women in Nigeria: The role of public libraries. Information and Knowledge Management, 5(4), 42-53.Tiemo, P., &Ateboh, B (2016). User’ Satisfaction with Library Information Resources and Services: A case study college of health sciences library Niger Delta University Amassoma Nigeria. Journal of Education 7 (16)United Nations Educational, Scientific and Cultural Organization (1994). UNESCO/IFLA Public Library Manifesto. Retrieved from: www.ifla.org/VII/s8/unesco/eng.htm WHO (2011).WorldHealthStatistics.Retrieved from: www.who.int//world_health_statistics/EN_/ WHO (2012).Adolescents: health risks and solutions. Retrieved from http://www.who.int/media- centre/fs360/ Retrieved October 13, 2014.WHO/UNAIDS (2006).AIDS epidemic update; special report on HIV/AIDS.Retrieved from: www.unaids.org//EpiRep/
Keywords: Information Service Provision; Public Libraries; PLWHA; Pharmaceutical Library; Nnewi